2016
DOI: 10.2139/ssrn.2858984
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Competition and Performance: Evidence from Real Tournaments

Abstract: There is a growing literature looking at how men and women respond differently to competition. We contribute to this literature by studying gender differences in performance in a high-stakes and male dominated competitive environment, expert chess tournaments. Our findings show that women underperform compared to men of the same ability and that the gender composition of games drives this effect. Using within player variation in the conditionally random gender of their opponent, we find that women earn signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 92 publications
1
20
1
Order By: Relevance
“…Exceptions are Booth and Nolen (2012) and Geraldes (2018), who similarly find that women avoid competing against men. Such a dislike is in line with evidence that women perform worse when they compete against men (Gneezy, Niederle and Rustichini, 2003;Günther et al, 2010;Backus et al, 2016;de Sousa and Hollard, 2016;Booth, Cardona-Sosa and Nolen, 2018;Booth and Yamamura, 2018).…”
Section: Conclusion and Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Exceptions are Booth and Nolen (2012) and Geraldes (2018), who similarly find that women avoid competing against men. Such a dislike is in line with evidence that women perform worse when they compete against men (Gneezy, Niederle and Rustichini, 2003;Günther et al, 2010;Backus et al, 2016;de Sousa and Hollard, 2016;Booth, Cardona-Sosa and Nolen, 2018;Booth and Yamamura, 2018).…”
Section: Conclusion and Discussionsupporting
confidence: 78%
“…Strategic interaction is typically ruled out by design in willingness-to-compete experiments, and how gender differences play out when the optimal choice depends on the anticipated behavior of competitors has therefore received even less attention. 2 This neglect is surprising in the light of the evidence that women perform worse when they compete with men (Gneezy, Niederle and Rustichini, 2003;Günther et al, 2010;Backus et al, 2016;de Sousa and Hollard, 2016;Booth, Cardona-Sosa and Nolen, 2018;Booth and Yamamura, 2018). Our study underlines the importance of considering the gender composition of the competitor base when investigating gender differences in willingness to compete.…”
Section: Introductionmentioning
confidence: 82%
“…Although these findings are inconsistent with Stafford’s, they are conceptually similar to the results of Backus, Cubel, Guid, Sanchez-Pages, and Mañas (2016), who examined computer-rated quality of moves in games by chess experts. After controlling for ranking, Backus et al showed that female players make moves of equal quality to male players when they play other women but make moves of lower quality when they play against men.…”
contrasting
confidence: 52%
“…Gerdes and Gränsmark (2010) take data from mixed-gender chess games and find that men not only are more risk-loving but also choose more aggressive opening strategies against women even if this reduces their probability to win the game. According to de Sousa and Hollard (2015) and Backus, Cubel, Guid, Sánchez-Pages, and Mañas (2016) women play worse against men in chess competitions.…”
Section: Literaturementioning
confidence: 99%